La « science-fiction bouffe » de Maïakovski. Autour de Mystère-Bouffe, La Punaise, Les Bains et de leur réception par le metteur en scène Antoine Vitez - Flore Garcin-Marrou (ReS Futurae)
The literary production of Mayakovsky, a figure of Russian avant-garde literature, is abundant and diverse. We know more about his poems or his involvement in Futurism than his four plays: Vladimir Mayakovsky (1913), Mystère- Bouffe (1918; 1921), The Bedbug (1929), The Bathhouse (1930). The last three plays are in line with Jules Verne and HG Wells' time travels: some characters are frozen and come resurrected in 1979, others have the opportunity to ride in a time machine that takes them 2030. These satires denounce what is is going on in political Russia: the transformation of revolutionary utopia into state realism - an authoritarian and repressive reality that will characterize the Stalinist era. The anticipation of a better politico-social world, time travel, cryogenics, fear of contamination, utopia, dystopia, eugenics are all themes that punctuate this corpus. The Bedbug and The Bathrooms are recognized in the SFE (The Encyclopedia of Science Fiction) as the “first significant original plays appeared in the 1920s and 1930s”. But it was when the French director Antoine Vitez (1930-1990) staged The Bedbug and The Bathrooms in the 1970s that he called them "Science Fiction Bouffe".